Communications, radar, and electronic warfare - Graham, Adrian W. (Hoboken, N.J. : Wiley, 2011)
'The book is structured systematically, enabling the reader to utilise the methods explained to improve radio spectrum exploitation in practice'--
Includes index.
Keywords: Radio wave propagation; Radio frequency; Wireless communication systems; TECHNOLOGY & ENGINEERING / Telecommunications